ASSOCIATIONS IN INTERGENERATIONAL FERTILITY BEHAVIOR AND PREFERENCES IN PUNJAB, PAKISTAN: TWO-GENERATION APPROACH - Yasir Rahim; Dr. Ayesha Chaudhry; Dr. Babak Mahmood; Dr. Zahira Batool (Policy Research Journal, 2025)
Background: The intergenerational transmission of fertility behavior and preference is a crucial aspect to consider, as it offers valuable insights into the complex factors that shape fertilitydecisions. Objective: To determine the associations in intergenerational fertility behavior and preference by using two-generation approach. Material and Methods: A cross-sectional research design was employed to investigate the intergenerational fertility behavior and preferences among mothers and their daughters in Punjab,Pakistan. A multistage sampling approach was utilized to select a representative sample of 2960 mother-daughter dyads from four districts in Punjab, namely Rajan Pur, Dera Ghazi Khan, Gujrat, and Jhelum. Data collection was facilitated through a digital application on android mobile devices, and the collected data was subsequently imported into SPSS version 26.0 for statistical analysis. Descriptive statistics and Pearson Correlation Coefficient were employed to examine the associations between the fertility behavior and preferences across the two generations. Results: This study compared the intergenerational fertility behavior and preferences of mothers and daughters in Punjab, Pakistan, revealing significant associations between various variables. The results showed that daughters had higher ages at first marriage and first birth, lower desired family sizes, and higher ever-use of contraceptive methods compared to mothers. The correlations between mothers' and daughters' fertility variables were moderate to weak, indicating a weakening of intergenerational associations over time. Conclusion: This study examines the intergenerational fertility behavior and preferences between mothers and daughters in Punjab, Pakistan, revealing a weakening of associations over time due to changing social, cultural, educational, and economic factors.